2010
DOI: 10.1002/pola.24330
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of main chain polymeric benzophenone photoinitiator via thiol‐ene click chemistry and Its use in free radical polymerization

Abstract: Main chain polymeric benzophenone photoinitiator (PBP) was synthesized by using “Thiol‐ene Click Chemistry” and characterized with 1H NMR, FTIR, UV, and phosphorescence spectroscopies. PBP as a polymeric photoinitiator presented excellent absorption properties (ε294 = 28,300 mol−1L−1cm−1) compared to the molecular initiator BP (ε252 = 16,600 mol−1L−1cm−1). The triplet energy of PBP was obtained from the phosphorescence measurement in 2‐methyl tetrahydrofurane at 77 K as 298.3 kJ/mol and according to phosphores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…14,15 Throughout the years, photopolymerization of thiol-enes has been shown both in industrial applications, including wearlayers in floor tiles, adhesives, coatings, electronics etc., and in academic applications for polymer synthesis, nanotechnology, biomaterials, lithography etc. [8][9][10][11][12][13][16][17][18][19][20][21] Thiol-ene photopolymerizations are typically described to proceed via a step-growth mechanism, 6,[22][23][24] and the reactions in thiol-ene photopolymerization can be generalized as seen in Scheme 1 below. 10 During the initiation step (1 and 2) a thiyl radical is formed as the SAH bond of a thiol group is cleaved.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Throughout the years, photopolymerization of thiol-enes has been shown both in industrial applications, including wearlayers in floor tiles, adhesives, coatings, electronics etc., and in academic applications for polymer synthesis, nanotechnology, biomaterials, lithography etc. [8][9][10][11][12][13][16][17][18][19][20][21] Thiol-ene photopolymerizations are typically described to proceed via a step-growth mechanism, 6,[22][23][24] and the reactions in thiol-ene photopolymerization can be generalized as seen in Scheme 1 below. 10 During the initiation step (1 and 2) a thiyl radical is formed as the SAH bond of a thiol group is cleaved.…”
Section: Introductionmentioning
confidence: 99%
“…20 Moreover, there may undergo photolysis reaction at CAS bond as that in type I aside from Habstraction reaction, 21 which could greatly enhance the photoinitiating efficiency. [22][23][24] Yin et al [25][26][27] synthesized a series of macroinitiator bearing BP and sulfur. However, little work has been done for preparing hyperbranched polymeric BPs containing both amine and sulfur via thiol-ene click chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…In the photochemical systems, photoinitiator plays a vital role in initiating the polymerization by generating active radicals under UV light irradiation through cleavage and hydrogen abstraction reactions [6]. Benzophenone and its derivatives are widely used as photoinitiator [7][8][9][10]. For example, Chung et al [11] reported that a series of urethane acrylate (UA) polymers had been prepared initiation by polyurethane (PU)-grafted benzophenone via photopolymerization method.…”
Section: Introductionmentioning
confidence: 99%